Secure and efficient authentication schemes for 5G heterogeneous networks - Ozhelvaci, Alican (Nanyang Technological University, 2022)
5G is a new paradigm that brings new technologies to overcome the challenges of the next-generation wireless mobile network. Also, 5G is expected to supply the fastest, most reliable mobile network access to support huge data traffic and massively connected nodes with low latency and high throughput. There are different new technologies that are emerging to tackle requirements of the future wireless mobile network, such as Network Function Virtualization (NFV), Software-Defined Networking (SDN), and cloud computing. The heterogeneous environment of 5G will cause frequent handoffs in small cells deployment where users join and leave frequently. Therefore, in this research work, the focus is on secure and seamless authentication mechanisms to supply strong, quick, and mutual authentication. And, careful attention is given to security challenges, therefore, potential pitfalls can be avoided. We will begin by explaining emerging technologies for the 5G mobile network. Then, the architecture of SDN is described in the 5G system. Subsequently, we will explain our proposed fast and efficient handover authentication schemes for next-generation wireless mobile communication - 5G – based on SDN architecture specified in the 3GPP technical standard release 16. Therefore, it can also support non-3GPP access networks too. All designed schemes are verified by security verification methods, we used the SPAN-AVISPA tool to simulate and analyze our proposed scheme and to provide a formal verification, and BAN Logic is used for logical correctness. Comparisons are shown for the proposed schemes with the existing protocol to show the improved security and performance. At last, a summary is drawn for the main contributions of this research work and the possible future works that new investigations should be done on other key areas to improve security features and performance of a security protocol or develop new ways to secure the protocol.